Attosecond pulse characterization - Laurent, Guillaume; Cao, Wei; Ben-Itzhak, Itzik; Cocke, Charles L. (My University, 2013)
In this work we propose a novel procedure for the characterization of attosecond pulses. The method relies on the conversion of the attosecond pulse into electron wave-packets through photoionization of atoms in the presence of a weak IR field. It allows for the unique determination of the spectral phase making up the pulses by accurately taking into account the atomic physics of the photoionization process. The phases are evaluated by optimizing the fit of a perturbation theory calculation to the experimental result. The method has been called iPROOF (improved Phase Retrieval by Omega Oscillation Filtering) as it bears a similarity to the PROOF technique [Chini et al. Opt. Express 18, 13006 (2010)]. The procedure has been demonstrated for the characterization of an attosecond pulse train composed of odd and even harmonics. We observe a large phase shift between consecutive odd and even harmonics. The resulting attosecond pulse train has a complex structure not resembling a single attosecond pulse once per IR period, which is the case for zero phase. Finally, the retrieval procedure can be applied to the characterization of single attosecond pulses as well.
Keywords: Attosecond pulses; Electron wave-packets; iPROOF